Moulting season corticosterone correlates with winter season bodyweight in an Arctic migrant bird. (22nd September 2020) - Doyle, Susan; Cabot, David; Furlong, John; Liu, Yixin; Colhoun, Kendrew; Walsh, Alyn J.; McMahon, Barry J.
Abstract : In vertebrates, the endocrine system translates environmental changes into physiological responses on which natural selection can act to regulate individual fitness and, ultimately, population dynamics. Corticosterone (CORT) and dehydroepiandrosterone (DHEA) are important regulators of the avian endocrine system but relatively few studies have investigated their downstream effects on key morphological fitness‐related traits in free‐living populations. This study quantified endocrine–morphology relationships in free‐living Greenland Barnacle Geese Branta leucopsis that breed in the high Arctic. CORT and DHEA were extracted from feather and blood samples and tested for relationships with three morphological traits associated with survival and reproduction: bodyweight, body size and facial plumage coloration. We expected CORT concentration to be higher in birds with less favourable morphological traits (i.e. lighter, smaller and less attractive) and DHEA to be higher in birds with more favourable traits (i.e. heavier, bigger and more attractive). As expected, individuals with higher CORT during the post‐breeding moult (July/August) had significantly lower bodyweight during the following winter (November–April). In contrast, we found no robust DHEA–morphology relationships and no statistically significant relationship between CORT and body size or facial plumage. Overall, this study provides evidence of a negative relationship between CORT and bodyweight extending across different seasons of the annual cycle in a long‐distance migrant. This is of particular interest because bodyweight fluctuates rapidly in response to environmental resources and is closely linked to both survival and reproductive success in this species. Understanding the relationship between CORT and key morphological traits is important because endocrine‐disrupting contaminants in the Arctic increasingly interfere with CORT function in birds, including Barnacle Geese, and based on the results of this study may have consequences for bodyweight regulation.